Sulfur Metabolism in the Extreme Acidophile Acidithiobacillus Caldus - Mangold, Stefanie; Valdés, Jorge; Holmes, David; Dopson, Mark (Frontiers in Microbiology, 2011)
Given the challenges to life at low pH, an analysis of inorganic sulfur compound oxidation was initiated in the chemolithoautotrophic extremophile Acidithiobacillus caldus. A. caldus is able to metabolize elemental sulfur and a broad range of inorganic sulfur compounds. It has been implicated in the production of environmentally damaging acidic solutions as well as participating in industrial bioleaching operations where it forms part of microbial consortia used for the recovery of metal ions. Based upon the recently published A. caldus type strain genome sequence, a bioinformatic reconstruction of elemental sulfur and inorganic sulfur compound metabolism predicted genes included: sulfide quinone reductase (sqr), tetrathionate hydrolase (tth), two sox gene clusters potentially involved in thiosulfate oxidation (soxABXYZ), sulfur oxygenase reductase (sor), and various electron transport components. RNA transcript profiles by semi-quantitative reverse transcription PCR suggested up-regulation of sox genes in the presence of tetrathionate. Extensive gel based proteomic comparisons of total soluble and membrane enriched protein fractions during growth on elemental sulfur and tetrathionate identified differential protein levels from the two Sox clusters as well as several chaperone and stress proteins up-regulated in the presence of elemental sulfur. Proteomics results also suggested the involvement of heterodisulfide reductase (HdrABC) in A. caldus inorganic sulfur compound metabolism. A putative new function of Hdr in acidophiles is discussed. Additional proteomic analysis evaluated protein expression differences between cells grown attached to solid, elemental sulfur versus planktonic cells. This study has provided insights into sulfur metabolism of this acidophilic chemolithotroph and gene expression during attachment to solid elemental sulfur.